Development of Therapeutic Small‐Molecule Fluorophore for Cell Transplantation. (10th October 2016) - Wang, Xin; Chen, Zelin; Luo, Shenglin; Jin, Taotao; Wang, Yu; Chen, Fuqin; Wu, Liao; Tan, Xu; Shi, Chunmeng
Abstract : Cell transplantation holds great promise in regenerative medicine but restricted cell survival and tracking severely limited their therapeutic efficacy. The development of multifunctional agents to simultaneously address these challenges will be very helpful in cytotherapy. Near‐infrared (NIR) imaging is being increasingly used for in vivo cell tracking, but the extensive cell contamination and potential cytotoxicity of current membrane lipophilic dyes severely limit their potentialuse in clinical applications. Here, a novel mitochondrial heptamethine dye, NIR cell protector‐61 (NIRCP‐61), is designed and synthesized via modification of N ‐alkyl side chains around a heptamethine core, which maintains the superior fluorescent imaging properties and significantly decreases cell contamination. Further, NIRCP‐61 also significantly alleviates cell damage from acute oxidative stress and improves their therapeutic outcome in multiple animal models. This cytoprotective effect is mediated by evoking the intracellular antioxidant defense mechanisms of nuclear factor erythroid 2‐related factor 2 (Nrf2) and phosphoinositide 3‐kinase/protein kinase B (PI3K/Akt) pathways. NIRCP‐61 is the first NIR agent that simultaneously meets the requirements for both cell tracking and cytoprotection. Therefore, NIRCP‐61 may represent an attractive therapeutic fluorophore for cell transplantation and offers a convenient way to impel potential translation in clinical cell‐based therapies. Abstract : A small‐molecule mitochondrial fluorophore, NIR cell protector‐61, is characterized and found to have unique optical imaging and cytoprotective properties for cell transplantation. The fluorophore enhances cell survival by inducing endogenous cytoprotective molecules against oxidative stress via activating nuclear factor erythroid 2‐related factor 2 and phosphoinositide 3‐kinase/protein kinase B pathways, and subsequently augments tissue repair and regeneration.